Ectopic Atrial Tachycardia in a 12-Month-Old Girl Treated With Ivabradine and Beta-Blocker, a Case Report - Holger Michel; Frank Heißenhuber; Sven Wellmann; Michael Melter; Stephan Gerling (Frontiers Media S.A., 2020)
We report on a 12-month-old girl with an ectopic atrial tachycardia successfully treated with the combination of a beta blocking agent and Ivabradine that acts on cardiac pacemaker cells by selectively inhibiting the If channel. Standard therapy had failed to control the tachycardia before. No side effects attributable to Ivabradine were noticed. Due to its mechanism of action Ivabradine is a promising novel agent for the therapy of tachycardia due to increased automaticity. Reports on the use of Ivabradine in young children or infants are rare, but show promising results for congenital junctional ectopic tachycardia. This report adds the second case of ectopic atrial tachycardia in this age group and novel treatment with Ivabradine to the literature.